FUTURES FOR FISHERIES PRODUCTION SYSTEMS IN WEST AFRICA: DEVELOPMENT OF SCENARIOS FOR ADAPTATION TO CLIMATE CHANGE - (:unkn) unknown (My University, 2010)
Literature gives strong evidence on the possible long term implications of climate change on oceans and inland-based fisheries. Climate change caused largely by accelerated global warming is likely to alter West African fisheries production systems that are already under stress from overexploitation and overcapitalization. The region is one of the most vulnerable due to the relatively importance of fisheries to national economies and diets, and limited capacity to adapt to potential impacts. This article draws on developing of scenarios for the West African region to identify the impacts of climate change and variability, through case studies in Ghana, Senegal and Mauritania, of which their territorial waters are located in the Canary and Guinea Current Large Marine Ecosystems where uncertainties exist on how future biophysical changes due to climate change will interact with other stressors and the anticipated responses and adaptation strategies for fisheries production systems. The study used qualitative expert interview and quantitative data (secondary and statistics), exploring the past and understanding the present to create narrative possible future attributed to climate change. Scenario developed through case studies facilitated understanding of the major drivers of changes in fisheries production systems and resulting effects in the context of climate change. It is envisaged that fishery –sector specific scenario need to be developed by taking into consideration the multiple drivers affecting fisheries production systems. Such development would enhance the region's ability and capacity to plan for adaptation within their sustainable fisheries management regimes as mitigation to the predicted great impacts of climate change.
Keywords: African Research